Erosion and Hot Corrosion Phenomena in Thermal Power Plant and their Preventive Methods: A Study - Kumar, Rakesh; Singh, Rajdeep; Kumar, Santosh (Asian Review of Mechanical Engineering, 2018)
Erosion and hot corrosion in coal fired boiler at elevated temperature is the primary reason behind downtime in power generating plants. In the present study an attempt has been made to study the basic concept of erosion, types, mechanism and tribological parameters that affect erosion wear. In addition, types and stages of hot corrosion have been discussed in brief with an emphasis on different protective methods for erosion such as use of super alloy, inhibitor, protective coating and hard facing. The distinct investigations have been carried to overcome the erosion and hot corrosion problems and found that erosion resistant coating and hard facing are effective way to resist degradations of erosion-corrosion (E-C) in a coal fired boiler.